Blood RNA expression of HSP70, GADD45a, and PA2G4 following somatic death in a mouse model for application in post-mortem interval estimation - Kaewkhammoon, Jutamas; Khacha-Ananda, Supakit; Narakornsok, Suteera (Journal of Medicine and Health Sciences, 2024)
Current tools for post-mortem interval (PMI) estimation include algor mortis, livor mortis, rigor mortis, and supravital reactions. However, the accuracy of these methods can be influenced by external environmental factors and the characteristics of the deceased body. To enhance precision, several studies have explored gene expression-based tools, as specific genes may exhibit upregulation or downregulation correlated with the time since death. This study aimed to investigate the use of postmortem blood RNA expression for PMI estimation. Heart blood samples were collected at 0, 0.5, 1, 6, 12, 24, and 48 hours postmortem. Total RNA was extracted, and gene expression was analyzed using quantitative real-time polymerase chain reaction (qRT-PCR). Results revealed that RNA quality and quantity for samples collected at 0, 0.5, and 1 hour postmortem ranged from 2.04 to 2.23 (A260/A280) and 30.16 to 44.67 µg/ml, respectively. Notably, the expression of HSP70 was significantly elevated at 0.5 hours postmortem, while the expression of GADD45a significantly decreased at 0.5 hours postmortem. Moreover, a significant association was observed between PMI and changes in delta cycle time for HSP70 (increase) and GADD45a (decrease). These findings suggest that HSP70 and GADD45a may serve as potential biomarkers for PMI estimation. However, further studies are required to validate the use of these genes in human postmortem samples for accurate and reliable PMI determination.